Modelo de reestructuración y optimización de los procesos logísticos utilizados en la cadena de abastecimiento de la comercializadora "Proveedora Olivia" - Cando Bonilla, Andrea Fernanda (2014)
Provider “Olivia” is a commercial business established in the 70 years with the vision of its founder, to offer products for home focused on a certain group of customers that was unattended, using a little-known funding mechanism then. It focuses on buying and selling home-appliances, technological products like mobile phones, computers and laptops, and also selling furniture, shoes, jewelry and toys at Christmas Time. Over time the business has expanded until become in a business that manages a local storage and warehouse in 3 cities... See attached file